Keanekaragaman Suku Asteraceae di Pinggir Danau Ranu Gumbolo Tulungagung - Nadiyyatul Husna; Winda Ashnaful Ma'rifah; Lilis Ilma Elvira; Azizah Wahyuningsih; Berliana Ayu Febriani; Indra Fardhani (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
Background: Asteraceae grows a lot in the tourist area of Lake Ranu Gumbolo Tulungagung and is not given much attention because it is only considered a wild plant. Hence, the utilization and management of these plants could be more optimal. This research aimed to identify the species diversity of the Asteraceae tribe on the shores of Lake Ranu Gumbolo, Tulungagung. Methods: The method used was to explore every corner of the observation location and calculate its diversity index. Results: A total of 8 species of the Asteraceae tribe have been identified on Lake Ranu Gumbolo, including Blumea balsamifera, Sphagneticola trilobata, Grangea maderaspatana, Ageratina Riparia, Ageratum conyzoides, Emilia sonchifolia, Tridax procumbens, and Eupatorium odoratum. The calculation of the diversity index showed that the species of the Asteraceae tribe at the observation site had a high diversity of 1.9. Conclusions: The results of this study can provide new knowledge about the plant diversity of the Asteraceae tribe, which readers or researchers can use as a source or reference. The results of this observation can be a different added value for Lake Ranu Gumbolo Tulungagung tourism and become an attraction for tourists.